Seismic geomechanics : how to build and calibrate geomechanical models using 3D and 4D seismic data - Herwanger, J. (Education tour series, 2011)
Three-dimensional geomechanical models have seen a rapid increase in use by the oil and gas industry, with applications from drilling to reservoir management. Yet few university programmes include applied geomechanics as part of their curriculum. This course aims to fill this gap and presents currently available methods to build, calibrate and interpret 3D and 4D geomechanical models.